“ESTRATEGIAS DIDÁCTICAS CON INFOGRAFÍA Y SU IMPACTO EN EL DESARROLLO COGNITIVO EN NIÑOS DE EDUCACIÓN INICIAL I” - OSTAIZA SOLORZANO CINTHIA MONSERRATE (2024)
A problem was evidenced about the lack of the use of infographics as a didactic strategy, which influences the cognitive development of students, being the objective of this research, to integrate the use of infographics as a didactic strategy, in the cognitive development of children of initial I. There are bibliographic supports that activities with infographics at an early age, they strengthen reading cognition and innate skills. Infographics represent, synthesize and explain a certain topic, taking more images, less text, shapes such as diagrams, concept maps and tables, amplifying their meaning by combining visual and linguistic resources, to capture attention and convey the message in a clear and concise way, encouraging creativity and forms of expression, through personalized visualizations, the understanding of information and interpretation of texts. The quantitative approach measures and analyzes statistics, the research method is inductive, based on reasoning, describing the problem and drawing conclusions from the reading corner and its impact on cognitive development. Consulting bibliographic citations and classroom observation, the possible solutions would be: create infographics that are attractive and valuable reading, with images, colors, key texts, increasing their vocabulary, reading comprehension and ability to concentrate. The research design is non-experimental, descriptive research type and mixed approach, which allows collecting information, facts or phenomena in their genuine context, without applying controlled changes, leading to an understanding of the problem, to then compare and analyze the quantitative and qualitative data collected from what was observed, with what was investigated by the experts in education, that interact and influence cognitive development. It is concluded that the benefits of reading infographics in students are: attractive, paying attention and shareable as a stimulus to the child's brain.